Comparative analysis of macular and peripapillary retinal nerve fiber layer thickness in normal, glaucoma suspect and glaucomatous eyes by optical coherence tomography - Saha, Mita; Bandyopadhyay, Sabyasachi; Das, Debabrata; Ghosh, Sourav (Nepalese Journal of Ophthalmology, 2017)
Introduction: Peripapillary retinal nerve fiber layer (RNFL) thickness analysis is a subjective method of analysis of glaucomatous damage. As almost 50% of retinal ganglion cells are located in the macula, assessment of macular thickness can be an alternative method for diagnosis of glaucoma. Objectives: To evaluate the changes in macular and retinal nerve fiber layer thickness in controls, glaucoma suspects and glaucoma patients using time domain optical coherence tomography (TD-OCT). Materials and methods: Macular and peripapillary RNFL scans were performed in one eye of 70 controls, 35 glaucoma suspects and 70 glaucoma patients by TD-OCT. The discriminating power of each parameter between the groups was determined by area under the receiver operating characteristic (AROC) curve. The correlation of macular thickness and RNFL thickness parameters with global field indices were also performed. P-value of < 0.05 was considered statistically significant. Results: The differences in all the macular thickness parameters between the groups were statistically significant (p< 0.05) except foveal thickness (FT) and nasal inner (NI) quadrant thickness. The temporal outer (TO) macular quadrant produced largest AROC curve of 0.90 between controls and glaucoma patients. The differences in all the RNFL thickness parameters were highly significant between the groups (p<0.001). The AROC curve between control group and glaucoma patients for RNFL average thickness was 0.99. Conclusion: Macular thickness as detected by TD-OCT had high discriminating power between controls, glaucoma suspects and glaucoma patients comparable with peripapillary RNFL thickness parameters.